2005
DOI: 10.1002/eji.200425799
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 and TLR2, but not TLR4, are required for host defense against Cryptococcus neoformans

Abstract: We investigated here the potential role of Toll-like receptors (TLR) and the adaptor protein MyD88 in innate immunity responses to Cryptococcus neoformans, a pathogenic encapsulated yeast. Peritoneal macrophages from MyD88 -/-or TLR2 -/-mice released significantly less TNF-a, compared with wild-type controls, after in vitro stimulation with whole yeasts. In contrast, no differences in TNF-a release were noted between macrophages from C3H/HeJ mice, which have a loss of function mutation in TLR4, relative to C3H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
133
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(150 citation statements)
references
References 34 publications
8
133
1
8
Order By: Relevance
“…In contrast, TLR4 was reported to sense glucuronoxylomannan, a major component of the polysaccharide capsule of Cn, in Chinese hamster ovary cells (15). Thus, the role of TLR2 and TLR4 in recognition of Cn remains to be fully understood, and some other TLR may be involved when considered along with the previous findings that the host-protective response was impaired in MyD88 Ϫ/Ϫ mice (12,13). The unmethylated CpG motif-containing DNA from prokaryotic microorganisms such as bacteria and viruses is known to trigger host immune responses by interacting with TLR9 (16 -18), which is distributed in the endosomal compartments (19,20).…”
Section: Ryptococcus Neoformans (Cn)mentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, TLR4 was reported to sense glucuronoxylomannan, a major component of the polysaccharide capsule of Cn, in Chinese hamster ovary cells (15). Thus, the role of TLR2 and TLR4 in recognition of Cn remains to be fully understood, and some other TLR may be involved when considered along with the previous findings that the host-protective response was impaired in MyD88 Ϫ/Ϫ mice (12,13). The unmethylated CpG motif-containing DNA from prokaryotic microorganisms such as bacteria and viruses is known to trigger host immune responses by interacting with TLR9 (16 -18), which is distributed in the endosomal compartments (19,20).…”
Section: Ryptococcus Neoformans (Cn)mentioning
confidence: 96%
“…Using mice genetically lacking MyD88 or TLR2 (MyD88 Ϫ/Ϫ or TLR2 Ϫ/Ϫ mice), it was revealed that MyD88 plays a critical role while TLR2 plays a relatively limited role in the response to Cn (12). In another study (13), TLR2…”
Section: Ryptococcus Neoformans (Cn)mentioning
confidence: 99%
“…For the quantification of IFN-␣4 and IFN-␤ mRNA, real-time quantitative RT-PCR assays were conducted, in duplicate, with an Applied Biosystems 7500 (Applied Biosystems), as described (37). PCR conditions were as follows: 50°C, 30 min; 95°C, 10 min; (95°C, 15 s; 60°C, 1 min) ϫ 40 cycles.…”
Section: Ifn-␣␤ Mrna Analysis By Quantitative Real-time Pcrmentioning
confidence: 99%
“…Real-time PCR data were normalized in each individual sample by the level of ␤-actin expression. Gene expression was measured by the comparative cycle threshold method (⌬⌬C T ) and was reported as the n-fold difference relative to the normalized expression of unstimulated samples (37). Primers and TaqMan MGB probes for ␤-actin, IFN-␣4, and IFN-␤ have been previously described (38,39) and were purchased from Applied Biosystems.…”
Section: Ifn-␣␤ Mrna Analysis By Quantitative Real-time Pcrmentioning
confidence: 99%
“…Cryptococcus neoformans (Yauch et al, 2004;Biondo et al, 2005). Contudo, outros trabalhos sugerem que o TLR2 e TLR4 não contribuem com a resposta do hospedeiro contra esse patógeno (Nakamura et al, 2006).…”
Section: Como Observado Com a C Albicans O Papel Do Tlr Na Infecçãounclassified